If it's not what You are looking for type in the equation solver your own equation and let us solve it.
.3.7(-83x-3) = 3.7(7x-30)
We simplify the equation to the form, which is simple to understand
.3.7(-83x-3)=3.7(7x-30)
Reorder the terms in parentheses
+(-24.9x-0.9)=3.7*(7x-30)
Remove unnecessary parentheses
-24.9x-0.9=+3.7+*(+7x-30+)
Reorder the terms in parentheses
-24.9x-0.9=+(+25.9x-111)
Remove unnecessary parentheses
-24.9x-0.9=+25.9x-111
We move all terms containing x to the left and all other terms to the right.
-24.9x-25.9x=-111 + 0.9
We simplify left and right side of the equation.
-50.8x=-110.1
We divide both sides of the equation by -50.8 to get x.
x=2.16732283465
| 3x+61=6x-11 | | 245-2x=43x+15 | | 5x-x=14*5 | | 6.7=-3.2+x | | 159-4x=23x+15 | | a=bc+d | | 96=5x^2-x^2 | | 41-7x=90 | | 1-5x-36x^2=0 | | 4x+1y=6 | | 3u^2-27= | | 2/1= | | 16-10w=-74 | | x-(x^2)=1 | | 5x+2x+x=8x^3 | | 5x+2x+x=8x | | 1/1= | | 64x=16x^3 | | 5x+2x+x=8 | | u^2+8u+16= | | 486=27r | | 1/-2= | | 17=1p-3-3p | | 3x-3y=15 | | a/4+3=-3 | | (x-2)(x+3)(3x+1)=0 | | 2x-80+x-50+13x+30=180 | | k/3-3=-11 | | v+8=13 | | 6x+10+14x=5x(1+4x) | | -1+2= | | m/7-9=5 |